MODEL OF STRENGTHENING THE ECONOMY OF RICE FIELD AGRO-TOURISM IN THE PASAR MELINTANG VILLAGE - Adelina Lubis; Indah Apriliya; Putri Anggi Oktavia Harahap; Nurul Wardani Lubis (SEAN Institute, 2022)
The development of agro-tourism is one alternative that can encourage regional economic potential. Pasar Melintang Village has the largest rice field in Lubuk Pakam, Deli Serdang. Village rice fields have the potential to be developed into agro-tourism so that they become a new alternative tourist destination in Deli Serdang. This research aims to formulate agro-tourism strategies and economic strengthening models in agro-tourism development. This research is a qualitative descriptive study, using SWOT analysis to formulate a marketing strategy for rice field agrotourism in Pasar Melintang Village. Partners in this study were 21 people from Mulia farmer groups, community leaders, and related institutions. The result of this research is the need for a diversification strategy of tourism products and participatory management in tourism development models